Music as a cultural claim in Lorca: Fortaleza sound festival - Alcolea Parra, María; Álvarez Santás, Silvia; Sánchez González, Olga (Street Art & Urban Creativity, 2025)
Tourism in the Region of Murcia has been based on the promotion of the sun and beach segment to attract visitors, but the overcrowding and exhaustion of the product has caused the search for new alternatives. The aim is to understand the integration of creativity and cultural industries as a local development plan in the city of Lorca to demonstrate the influence of celebrating a festival in improving tourism promotion. The methodology with a qualitative approach includes a review of the literature for the descriptive study combined with the interview technique with managers and representatives of the music sector. It is concluded that the celebration of the Fortaleza Sound festival has allowed the integration of strategic local competition needs and solutions for the economic development of Lorca. The positioning during its first edition has contributed to consolidate the foundations for future digital advertising strategies.